2013
DOI: 10.1063/1.4824367
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of high density arrays of silicon nanowire field effect transistors

Abstract: Articles you may be interested inPalladium nanoparticle decorated silicon nanowire field-effect transistor with side-gates for hydrogen gas detection Appl. Phys. Lett. 104, 013508 (2014) Proximity effect corrected e-beam lithography of hydrogen silsesquioxane on silicon on insulator was used to fabricate multi-channel silicon nanowire field-effect transistors (SiNW FETs). Arrays of 15-channels with a line width of 18 nm and pitch as small as 50 nm, the smallest reported for electrically functional devices, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The pitch size plays a role in the sensing performance. For example, a small pitch size array was shown to have reduced sensing performance due to the fringing capacitance and low electrostatic field resulting from the applied back gate voltage [ 128 ]. Although the total sensing area of arrays are larger than that of NWs, the device overall sensitivity is still complex and depends on whether the detection is reaction limited or near the end of detection equilibrium.…”
Section: Sensing Performance: Finding the Best Compromise Among Simentioning
confidence: 99%
“…The pitch size plays a role in the sensing performance. For example, a small pitch size array was shown to have reduced sensing performance due to the fringing capacitance and low electrostatic field resulting from the applied back gate voltage [ 128 ]. Although the total sensing area of arrays are larger than that of NWs, the device overall sensitivity is still complex and depends on whether the detection is reaction limited or near the end of detection equilibrium.…”
Section: Sensing Performance: Finding the Best Compromise Among Simentioning
confidence: 99%
“…Among the silicon nanostructures, silicon nanowires (SiNWs) are highly considered due to their thermoelectric, optical, electrical and thermal properties and a great deal of researches have been focused on fabrication, investigation and applications of these nanostructures. It is shown that silicon nanowire field effect transistors (SiNWFETs) [1][2][3] can be a reliable candid for biosensors which they are real-time, high selective and high sensitive [4][5][6]. They are also a nice choice for advanced energy storage and conversion devices [7] such as lithium-ion rechargeable batteries [8][9][10], photovoltaic devices [11][12][13], and thermoelectric devices [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Negative resist-hydrogen silsesquioxane (HSQ) has been used as a mask against dry etching. HSQ converts into silicon dioxide during electron beam exposure, which is then thermally cured to increase the stability against dry etching [18][19][20][21][22][23] and act as an insulating layer to prevent the Hall contact electrode from shorting [14]. The angled deposition technique, where the NWs are used as a shadow mask, is utilized for Hall electrode formation.…”
Section: Multiple Contacts Investigation Of Single Silicon Nanowires ...mentioning
confidence: 99%